Stop! Check your initial assumptions: Frozen patient management in obstetrical practice. Issue 50 (December 2017) - Kobo-Greenhut, Ayala; Sakas, Jawad; Magnezi, Racheli; Ben Shlomo, Izhar
Abstract : Abstract: At times, leaping from one patient management routine to an alternative one may be required to mitigate medical errors. "Frozen patient management" is the resultant situation, when, in the face of an obvious gap between the expected and the actual phenomena, leaping from current patient management to an alternative one is not considered or done. Frozen patient management can lead to a significant delay of the correct definitive intervention, be it surgical or pharmacological. The significance of this delay is especially important in time-dependent dynamic situations. In delivery ward, this may cost the life of either the fetus or the mother. In this study, we describe a sequence in which frozen patient management occurred in the delivery ward. Using "thinking protocol" (herein termed "de-freezing" questionnaire) made the team stop and consider a leap when gaps became apparent, and saved the mother's life. We believe that adopting the "de-freezing questionnaire" as a routine adjunct for all medical activities would lead to a timely change of treatment line, which, in turn, will save lives and unnecessary suffer.